Midwifery Continuity of Care with the Use of Oxytocin Massage in the Postpartum Period - Neng Seli Fitriani; Sri Mulyati; Ida Widiawati; Yulinda Yulinda (FORIKES, 2026)
Continuity of care in midwifery refers to comprehensive services provided continuously from pregnancy, childbirth, postpartum, breastfeeding, newborn care, and family planning. This study aimed to evaluate the application of oxytocin massage for postpartum mothers within the framework of continuity of care. The study employed a case report design using continuous midwifery management based on scientific evidence and was conducted from August to November 2024. The subject was a pregnant woman at 37 weeks of gestation who was followed until participation in postpartum family planning. The results of care were reported descriptively. During pregnancy, several problems were identified, including sleep disturbance, back pain, overweight status, mild anemia, and Braxton Hicks contractions. Intrapartum care focused on pain management using a birth ball. During the postpartum period (day 12 postpartum), insufficient breast milk production was identified. The intervention provided was oxytocin massage to improve milk production and flow. After the intervention, a significant improvement was observed, indicated by a questionnaire score increasing from 3 (poor milk flow) to 8 (adequate milk flow). In newborn care, weight loss was identified at 12 days of age, and education and counseling on infant nutrition were provided. For family planning care, Mrs. F chose an implant contraceptive method. All identified problems were successfully managed. As conclusion, continuity of care in midwifery combined with the application of oxytocin massage was effective in addressing maternal and neonatal problems, particularly in improving breast milk production and supporting successful breastfeeding outcomes.Keywords: continuity of care; breastfeeding; postpartum period; oxytocin massage